Enseigner l’éducation comparée en vue de développer des compétences : Évolution des savoir agir en situation - Calvin, Bipoupout Jean (IJRDO- Journal of Educational Research, 2018)
In a context characterized by globalization and the development of learners’ competences, one the pertinent orientation o the teaching of comparative education in schools could be the one consisting on teaching comparative education to develop competences in the perspective of a globalized system. In order to facilitate the development of competences in comparative education, one of the questions to be answered is: how could we conceive the evolution of competences at the level of primary education, at the level of teacher training colleges and at the level of higher teacher training colleges or at the level of faculties of education? That is the main question which is examined in this study. From the observation of teaching practices while training teachers in teacher training colleges, teaching experiences while teaching students at different level of education; from interviews, documents analysis, the study suggests a set of actions and activities that is centered on the integrative approach of pedagogy, of training and of didactics. Résumé Dans un contexte caractérisé entre autres par la mondialisation et le développement des compétences chez les apprenants, l’une des orientations pertinente de l’enseignement de l’éducation comparée pourrait être l’enseignement de l’éducation comparée en vue de développer des compétences dans la perspective d’un système mondial. Dans le but de parvenir à la facilitation de l’apprentissage et du développement des compétences en éducation comparée, l’une des questions auxquelles il faut apporter une réponse est de savoir comment évoluent les savoir agir en situation à l’école primaire, dans les institutions de formation des instituteurs et dans les Ecoles normales supérieures ou les facultés d’éducation? Telle est la principale interrogation qui est examinée dans cette étude. À partir de l’observation participante dans le cadre de la formation d’enseignants, de l’enseignement des élèves de différents niveaux; des entrevues, de l’étude de documents, l’étude suggère un ensemble d’actions et d’activités centré sur une approche intégratrice de la pédagogie, de la formation et de la didactique.